Growth of Railway Network in China (1988-2002) - Serguei Tarkhov (Promet - Traffic&Transportation, 1970)
20. 000 km of new railways were built in China in1988-2002. The railway network has increased its topologicalcomplexity from 75 to 112 circuits and the new 3nt topologicallayer appeared in 1993 and the 4'h will emerge in 2004 after the opening of the rail ferry Dalian - Yan-tai. The main features ofthe recent Chinese rail network are: 1) the predominance ofmeridional-ity, 2) the spatial disproportion between the easterncoastal area (with dense network) and the empty western part,3) the low level of electrification (20%) and the low share ofdouble-track sections (30%), 4) the land-lock orientation ofthe whole network and a small number of lines along the seacoasts. These disproportions are the main obstacles for a harmonicspatial devel-opment of the economic structure.